Life of Fred. Begin teaching - Schmidt, Stanley F. (Stanley Fredric), 1944- (Reno, Nevada : Polka Dot Publishing, 2013)
You will learn the uses of the 12 tenses in English, what are the 16 ways to make plurals, why since is a dangerous word, the definition of existentialism, and about reading Moby Dick at a deeper level.
Meeting Mack -- Teachers quit -- Today -- Arrival at night -- Searching for lesson plans -- In custody -- Helping Margie -- Intake -- Rabbits and kangaroos -- What we know -- Early morning -- The proofreading room -- Pineapple invasion -- Subject-verb -- College -- In the classroom -- Begin teaching -- Into the deep -- six tenses in four pages.
Includes index.
N/A mc
Keywords: Language arts (Elementary) -- Problems, exercises, etc; Language arts -- Problems, exercises, etc; Home schooling -- United States; Home schooling -- Curricula